Synthesis of single and interplant non-isothermal water networks. - Ibrić, Nidret; Ahmetović, Elvis; Kravanja, Zdravko; Maréchal, François; Kermani, Maziar (Journal of Environmental Management)
This paper addresses the synthesis problem of non-isothermal water networks using a mathematical programming approach. A heat-integrated water network superstructure and its corresponding mixed integer nonlinear programming (MINLP) model is proposed for the synthesis of individual as well as interplant water networks. A new feature of the proposed model includes piping installation cost within the objective function minimising the total annual cost of the network. This introduces additional trade-offs between operating and investment costs that can impact a final network design. Three examples were solved in order to demonstrate the applicability and effectiveness of the proposed model and solution approach. The results show that additional saving in total annual cost can be achieved by enabling direct water integration between plants. Improved solutions were obtained compared to those reported in the literature considering freshwater and utilities consumption as well as total annual cost.